Metabolic Syndrome: the Influence of Adipokines on the L-Arginine-NO Synthase-Nitric Oxide Signaling Pathway - L. A. Kuznetsova (Acta Biomedica Scientifica)
Metabolic syndrome includes the following symptoms: obesity, hyperlipidemia, hypertension, insulin resistance, and cardiovascular disease. The purpose of this review is to elucidate the role of adipokines in the regulation of the L-arginine-NO-synthas-NO signaling pathway in the pathogenesis of metabolic syndrome. The main questions raised in the review are: how adipokine secretion changes, how the level of their receptors is regulated, and which signaling pathways are involved in the transmission of adipokine signals when coupled to the L-arginine-NO-synthase-NO signaling cascade. Adipokines are peptide hormones that transmit a signal from adipose tissue to targets in the brain, blood vessels, liver, pancreas, muscles, and other tissues. Some adipokines have anti-inflammatory and insulin-sensitive effects: adiponectin, omentin, adipolin, chemerin, progranulin. Others have the negative inflammatory effect in the development ofmetabolic syndrome: visfatin, vaspin, apelin. Adipokines primarily regulate the expression and activity of endothelial NO-synthase. They either activate an enzyme involving 5-AMP protein kinase or Akt kinase, increasing its activity and synthesis of NO in the tissues of healthy patients: adiponectin, adipolin, omentin, or inhibit the activity of eNOS, which leads to a decrease in NO-synthase and suppression of mRNA bioavailability: vaspin, visfatin, apelin in metabolic syndrome, and a decrease in its activity leads to dissociation and endothelial dysfunction. It should be noted that the bioavailability of NO formed by NO-synthase is affected at many levels, including: the expression ofNO-synthase mRNA and its protein; the concentration of L-arginine; the level of cofactors of the reaction; and to detect the maximum activity of endothelial NO-synthase, dimerization of the enzyme is required, posttranslational modifications are important, in particular, phosphorylation of endothelial NO-synthase by serine 1177 with the participation of 5-AMP protein kinase, Akt kinase and other kinases. It should be noted that the participation of adiponectin, omentin, and kemerin in the regulation of the L-arginine-NO-synthase-NO cascade in metabolic syndrom opens up certain opportunities for the development of new approaches for the correction of disorders observed in this disease. The review analyzes the results of research searching in PubMed databases, starting from 2001 and up to 2020 using keywords and adipokine names, more than half of the references of the last 5 years.